2021
DOI: 10.1530/eje-21-0668
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A and parafibromin expression in parathyroid carcinoma

Abstract: Objective: Parathyroid carcinoma (PC), atypical parathyroid tumors (APT) and parathyroid adenoma (PA) present with hypercalcemia. Diminished calcium-sensing receptor (CaSR) expression is reported in PC but is rare in benign tumours. Filamin A (FLNA) binds to the CaSR and activates the mitogen-activated protein kinase (MAPK) signalling pathway. FLNA is related to tumour aggressiveness in several cancers, but its role in parathyroid neoplasia is unknown. Design: We examined FLNA, CaSR and parafibromin express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The filamin A (FLNA) gene encodes the homonym filamin A protein, a non-muscle actin filament cross-linking scaffold protein that influences the intracellular localization of numerous proteins. A very recent study by Storvall et al (35) found that PCs were characterized by significantly increased cytoplasmic FLNA expression, compared to both PAs and atypical parathyroid adenomas (aPAs), suggesting that the increased cytoplasmic, and membranous, FLNA expression could be a marker of malignancy, and a potential prognostic predictor of aggressive behavior in parathyroid neoplasms, mostly in combination with parafibromin expression. However, a previous study (36) showed opposite results, reporting a decreased expression of full-length FLNA in the cytoplasm of tumoral parathyroid epithelial cells, both for PAs (50% to 10% of FLNA-positive cells) and PCs (less than 10% or totally absent FLNA-positive cells), with respect to the normal parathyroid counterpart.…”
Section: Flna Genementioning
confidence: 99%
“…The filamin A (FLNA) gene encodes the homonym filamin A protein, a non-muscle actin filament cross-linking scaffold protein that influences the intracellular localization of numerous proteins. A very recent study by Storvall et al (35) found that PCs were characterized by significantly increased cytoplasmic FLNA expression, compared to both PAs and atypical parathyroid adenomas (aPAs), suggesting that the increased cytoplasmic, and membranous, FLNA expression could be a marker of malignancy, and a potential prognostic predictor of aggressive behavior in parathyroid neoplasms, mostly in combination with parafibromin expression. However, a previous study (36) showed opposite results, reporting a decreased expression of full-length FLNA in the cytoplasm of tumoral parathyroid epithelial cells, both for PAs (50% to 10% of FLNA-positive cells) and PCs (less than 10% or totally absent FLNA-positive cells), with respect to the normal parathyroid counterpart.…”
Section: Flna Genementioning
confidence: 99%
“…Cytoplasmic expression of filamin A was statistically significantly higher in carcinomas compared to atypical adenomas or adenomas [165]. The expression of filamin A also correlated with the serum levels of calcium and PTH, but was not associated with Ki-67 indicating that filamin A plays significant role in calcium turnover but is not associated with the degree of anaplasia [165]. Indeed, Mingione et al, demonstrated that loss of filamin A reduces CaSR expression in protein and mRNA levels; the CaSR-induced ERK phosphorylation also decreases [169].…”
Section: Calcium-sensing Receptor (Casr) and The Associated Molecular...mentioning
confidence: 88%
“…Scaffold protein filamin A binds to calcium-sensing receptor and activates the mitogenactivated protein kinase MAPK pathway. Cytoplasmic expression of filamin A was statistically significantly higher in carcinomas compared to atypical adenomas or adenomas [165]. The expression of filamin A also correlated with the serum levels of calcium and PTH, but was not associated with Ki-67 indicating that filamin A plays significant role in calcium turnover but is not associated with the degree of anaplasia [165].…”
Section: Calcium-sensing Receptor (Casr) and The Associated Molecular...mentioning
confidence: 89%
See 2 more Smart Citations